Inter-platelet communication driving thrombus formation is regulated by extracellular calpain-1 cleavage of connexin 62 - Kirk A. Taylor; Amro Elgheznawy; Recep Adiyaman; Tyler L. Horn; Sarah Parkes; Craig E. Hughes; Liam J. McGuffin; Jonathan M. Gibbins (Haematologica, 2025)
Connexin (Cx) gap junction proteins are expressed by a multitude of cells and function as plasma membrane hemichannels or dock to form intercellular communication tunnels. Whilst Cx43 has garnered considerable attention, less is known about the structure and function of Cx62 channels. Platelets and megakaryocytes express Cx37, Cx40 and Cx62, which contribute to hemostatic and thrombotic responses. Our study explores an unexpected finding that following platelet activation, an extracellular region of Cx62 undergoes proteolytic cleavage by calpain-1. We adopted an interdisciplinary approach to evaluate structural and functional consequences of calpain-mediated cleavage of Cx62. Cellular signaling was assayed by immunoblotting, aggregation and calcium flux assays. Gap junction function and thrombus formation were assessed under arteriolar flow. In silico modelling was used to predict calpain-mediated changes to the pore diameter and design a decoy peptide (62Pept-NT). Mechanistically, Cx62 cleavage is Ca2+-dependent and requires calpain-1 externalization. Modelling a predicted calpain-1 cleavage site on the first extracellular loop, shows that calpain can dock to Cx62 monomers, promoting stepwise channel cleavage. Consequently, we predict a significant pore dilation enhancing diffusion of signaling molecules between cells and into the extracellular milieu. We designed a decoy peptide that abrogated calpain-1-mediated cleavage, reduced intercellular communication and restricted thrombus growth. Cx62 cleavage was dependent upon sequential action of protein kinase A, protein phosphatase 2A and Ca2+ release from intracellular stores. Extracellular calpain cleavage represents a fundamentally new regulatory mechanism for connexin 62, culminating in an irreversible open state.